Makna Kehilangan Orangtua Bagi Remaja di Panti Sosial Bina Remaja Indralaya Sumatera Selatan; Studi Fenomenologi - suzanna, suzanna (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2018)
Losing is a condition who has ever been in individual a long life. The objective of the research was to find the meaning of parents losing for adolescent of social home at Bina Remaja. It was important in adolescents respon to have parents losing process and also adaption in Life Phase Qrowth. The Qualitative research  used Phenomenology Study with Indepth Interveiw and Field Notes by involved six informans. The result of the study found there were five themes losing parents such as : The deep sadness in different scale, losing parents figure, lack of affections, there is no one to share, and the unbreakable family condition. The losing Phases were denial, anger, and acceptance. In conclusion the deep sadness in adolescentt  was found hey can accept it. Hoping and Praying of adolescent is kind of their love to them.